(3TeS GdYdhe hOhGA cdGe GdYQH ef Gdcdhes - (3fThGf Hf SYjO GdMejQj, CHh SYjO,J (B573 (3g` s ((3YHO GdbGOQ Hf YH(B\(3O Gddg GdSdei s)
(3ChdgG (B:s
(3ef cJGH GdUGO , HGH GdUGO heG HYOgG ef GdMQha ef GdeVGYa GdCSeGA (B: (3aYd HaJM GdaGA H (B: (3QLd UH EPG YdJg Gdghi O (B: (3GdUO GdLHd s
(3HgG fXGe GdJYbjHIs
(3HOGNdgG HYV GdJbWjY JJab ai BNQgG eY BNQ GdLRA GdKGfi ef fSNI NRGfI GdEeGe jMji Hf eMeO Hf jMji (B- (3UfYGAs
(3fSNI MGOjI YTQIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GddZIs